POS07 Reduced ADAMTS-13 activity levels in partial anterior circulation transient ischaemic attack patients compared to nonstroke controls. Issue 11 (22nd October 2010) - Frentzou, G A; Kamara, C; Harkness, K A; Haddock, G; Doyle, C; Taylor, M; Venables, G S; Woodroofe, M N; Cross, A K; Randall, M
Abstract : Clarification of the pathophysiological mechanisms of intra-arterial thromboembolism may lead to novel treatments for cerebrovascular disease. There is increasing evidence for the role of von Willebrand factor (VWF) cleaving protease (ADAMTS-13) in modulating the thrombotic cascade in high flow arterial settings. VWF multimers are rich in ultra large forms (ULVWF) which can rapidly bind its primary platelet receptor resulting in spontaneous aggregation of platelets. Under normal conditions, these ULVWF are regulated by rapid proteolysis converting them to smaller, less active forms. The protease responsible for cleavage of ULVWF is ADAMTS-13. We measured the ADAMTS-13 antigen and ADAMTS-13 activity levels in the plasma of consecutive patients with transient ischaemic attack (TIA), compared with nonstroke controls, in a hospital based TIA clinic. This was compared with VWF levels. Samples were analysed in the acute phase and at 3 months postevent. In our pilot study patients with partial anterior circulation type TIAs had significantly reduced ADAMTS-13 activity compared to controls (p=0.0394). No significant differences were seen between high- and low-risk ABCD2 scored patients. We did not observe any significant changes in VWF levels in our study sample. Our pilot study suggests a potential role for altered ADAMTS-13 activity in the pathophysiology of TIA.